Efektifitas Antibiotik Pasien Demam Tifoid RSUP Dr. M. Djamil Padang - Ayu Rahmawati; Husni Muchtar; Hansen Nasif (JURNAL FARMASI DAN MAKANAN, 2019)
To find out the effectiveness of antibiotics in typhoid fever patients at the SMF of Pediatric and SMF in Internal Medicine Dr. RSUP M. Djamil Padang. This study was a cross-sectional study with a retrospective type of data during 2012 and prospective from June to September 2013, with a descriptive analysis design. The number of patients who met the inclusion criteria were 11 patients. Percentage of antibiotic use in adult patients for ceftriaxone (60%) and chloramphenicol (40%). The percentage of antibiotic use in pediatric patients for ceftriaxone, chloramphenicol, and cefixim are 60%, 27%, and 13%, respectively. Fever free for ceftriaxone and chloramphenicol in pediatric and adult patients, each of which is 2-3 days and 4-6 days; 3-4 days and 4 days. To be free of cefixime fever in pediatric patients is 2 days. The length of treatment required is ceftriaxone and chloramphenicol (children and adults) antibiotics, 6 - 13 days and 9-13, respectively; 11-14 and 7 days. For the duration of cefixime antibiotic treatment for children is 13 days. The results of this study indicate that antibiotics that are used effectively against typhoid fever patients are seen from the time of free of fever and length of stay.